Proceedings and Papers of the Seminar on Land Reforms-A Retrospect and Prospect - Planning Commission (Planning Commission, 1989)
A two-day Seminar on ‘Land Reforms—A Retrospect and Prospect’ was organised by the Rural Development Division of the Planning Commission with the object of bringing together eminent economists, civil servants, and field workers. The seminar reviewed the implementation of various land reforms legislation with the aim of drawing lessons for future. In particular, it focused on the policies related to tenancy, ceiling, redistribution of land, maintenance of land records, consolidation of holdings, and protection of interests of weaker sections and women, Scheduled Castes, and Scheduled Tribes.
Planning Commission, Government of India
Planning Commission, Government of India